Social Marketing Campaign in Tobacco Cessation to Young Adults - Adhianty Nurjanah, Yeni Rosilawati,; Sugiyo, Dianita; Nurmandi, Achmad; Habib, Shahid (Opción, 1970)
This study will evaluate the social marketing strategy to influenceyoung adults by taking a case study in Klungkung Regency in BaliProvince, Indonesia. This research specifically interested in looking atthe social marketing strategy including channel analysis, marketsegmentation and audience analysis, considerations of product, price,place and promotions), implementation and evaluation of TobaccoControl Behavior. The study found that the social marketing using 4P(Product, Price, Place and Promotions) +additional 2P (Partnership andPolicy) elements of social marketing. The product is the idea of healthylife, preventing is more worthy than cure. The price is the change ofbehaviour, from smoking to quit smoking, and to prevent the earlysmokers. The distribution channel is family and community support.The partnership is using community elements, among others,community leaders starting from Banjar (village), PKK (Family Welfare Program) mothers, Posyandu (Integrated Service Post) cadres and religious leaders. Finally the policy is the local regulations (Perda)Number 10 of 2011 concerning Smoke Free Area.